Effects of germanium organic compound and α-lipoic acid on STZ-induced diabetes manifestations in rats - Rozhkovskyi, Y. (Regulatory Mechanisms in Biosystems, 2024)
Deep deteriorations accompany diabetes in all types of metabolism with an impact on functional activity and complications that are of vital significance. Damage to the liver contributes to the worsening of the patient’s state. Oxidative stress makes a pivotal contribution to diabetes-induced liver disorders. The investigation of niacin-oxyethylidene-diphosphonate germanate (MIGU-4) and α-lipoic acid treatment, which both possessed antioxidative properties upon the functional state in rats with streptozotocin induced diabetes, was the aim of the investigation. Treatment with MIGU-4 (25.0 mg/kg, i.p.) and α-lipoic acid (50.0 mg/kg, i.p.) started six weeks after induction of diabetes by streptozotocin (65.0 mg/kg, i.p.) administration.and was performed daily for a further six weeks. The results obtained revealed that combined administration of MIGU-4 (25.0 mg/kg) and α-lipoic acid (50.0 mg/kg) caused an increase of albumin and a decrease in bilirubin when compared with streptozotocin-treated rats. Administration of MIGU-4 and α-lipoic acid caused the reduction of cholesterol and triglycerides, low-density lipoproteins, while high-density lipoproteins increased. Besides, treatment with MIGU-4 and α-lipoic acid reduced the malone dialdehyde, increased reduced glutathione content, increased the superoxide dismutase and catalase activity compared with the streptozotocin-diabetes. The protective effect of combined treatment is more pronounced than that caused by α-lipoic acid (50.0 mg/kg) treatment alone. There is ample scope for further investigations of MIGU-4 in treating diabetes-induced liver damage and complex metabolic disorders.